2009
DOI: 10.1128/aac.00012-09
|View full text |Cite
|
Sign up to set email alerts
|

Protein Kinase G Is Required for Intrinsic Antibiotic Resistance in Mycobacteria

Abstract: Antibiotic resistance and virulence of pathogenic mycobacteria are phenotypically associated, but the underlying genetic linkage has not been known. Here we show that PknG, a eukaryotic-type protein kinase previously found to support survival of mycobacteria in host cells, is required for the intrinsic resistance of mycobacterial species to multiple antibiotics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
68
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(69 citation statements)
references
References 29 publications
(38 reference statements)
0
68
1
Order By: Relevance
“…DCGen3002-1 encoded a protein similar to phosphomannomutase and DCKan30A29 encoded a protein similar to nucleotide sugar dehydrogenase, both of which are responsible for alginate polymerization and the resultant alginate layer would cause a mucoid phenotype and provide a protective barrier against host immune defenses and antibiotics (May et al, 1991;Naught et al, 2002). DCKan30A03 encoded 2-oxoglutarate dehydrogenase is involved in glutamine utilization and could reduce cell wall hydrophobicity, which has previously been reported to be important for multiple antibiotic resistance (Wolff et al, 2009). Efflux pump mediated resistance was found in ABC transporter like protein encoded DCKan30A31-2.…”
Section: Aminoglycoside Resistancementioning
confidence: 99%
“…DCGen3002-1 encoded a protein similar to phosphomannomutase and DCKan30A29 encoded a protein similar to nucleotide sugar dehydrogenase, both of which are responsible for alginate polymerization and the resultant alginate layer would cause a mucoid phenotype and provide a protective barrier against host immune defenses and antibiotics (May et al, 1991;Naught et al, 2002). DCKan30A03 encoded 2-oxoglutarate dehydrogenase is involved in glutamine utilization and could reduce cell wall hydrophobicity, which has previously been reported to be important for multiple antibiotic resistance (Wolff et al, 2009). Efflux pump mediated resistance was found in ABC transporter like protein encoded DCKan30A31-2.…”
Section: Aminoglycoside Resistancementioning
confidence: 99%
“…The loss of pknG function has been previously implicated in the increased sensitivity of M.smegmatis to multiple antibiotics (65) , perhaps due to a decrease in cell wall hydrophobicity. In addition, quantitative RT-PCR (Figure 4) revealed that icl1 (encoding isocitrate lyase, part of the glyoxylate bypass), narX (involved in nitrate reduction), and tgs1 (a triacylglycerol synthase) were all NRP2 and INH-responsive.…”
Section: Use Of Transcriptional Profiling To Screen For Nrp and Inh-rmentioning
confidence: 99%
“…Minimum inhibitory concentrations (MICs) of selected mutants to antifolates were determined by serial dilution assays (see below). Mapping of transposon insertion sites in the mutants by using an arbitrary PCR method was carried out as described previously (16,18).…”
mentioning
confidence: 99%
“…The entire open reading frame of M. smegmatis msmeg_5472 was deleted using the recombineering method as described previously (18). The 616-bp DNA region upstream of msmeg_5472 was PCR-amplified using primers fuel-Del1 and fuel-Del2 (supplemental Table S2).…”
mentioning
confidence: 99%
See 1 more Smart Citation